2020
DOI: 10.1530/eje-19-0620
|View full text |Cite
|
Sign up to set email alerts
|

Serum insulin levels are associated with vulnerable plaque components in the carotid artery: the Rotterdam Study

Abstract: Background To investigate the association between fasting serum insulin and glucose levels with atherosclerotic plaque composition in the carotid artery. Impaired insulin and glucose levels are implicated in the etiology of cardiovascular disease; however, their influence on the formation and composition of atherosclerotic plaque remains unclear. Methods In 1740 participants (mean age 72.9 years, 46% women, 14.4% diabetes mellitus) from the population-based Rotterdam Study, we performed carotid MRI to evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…Consequently, energy production from free fatty acids oxidation will increase and lipotoxicity may occur, leading to increased oxygen consumption, stress, and reduced cardiac contractility (28). Alternatively, serum insulin levels were associated with a higher presence of intraplaque hemorrhage in existing atherosclerotic plaque (29), a plaque feature responsible for plaque progression in coronary arteries (30), leading to RV coronary ischemia (31). However, the link between the RV function and pulmonary circulation remains poorly understood (14).…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, energy production from free fatty acids oxidation will increase and lipotoxicity may occur, leading to increased oxygen consumption, stress, and reduced cardiac contractility (28). Alternatively, serum insulin levels were associated with a higher presence of intraplaque hemorrhage in existing atherosclerotic plaque (29), a plaque feature responsible for plaque progression in coronary arteries (30), leading to RV coronary ischemia (31). However, the link between the RV function and pulmonary circulation remains poorly understood (14).…”
Section: Discussionmentioning
confidence: 99%
“…In the Rotterdam study, a large population study of individuals with ≥2.5 mm plaque, it was shown that systolic blood pressure and pulse pressure were significantly positively associated with IPH (OR: 1.13, 95% CI: 0.99-1.28; OR: 1.22, 95% CI: 1.07-1.40, respectively) after adjustment for age and sex (139). The serum insulin levels are also associated with IPH (OR: 1.42, 95% CI: 1.12-1.7), while they were not associated with the presence of calcifications or a LRNC (140). Recently, Pletsch-Borba et al (141) showed in a sub-analysis of 198 participants of the Rotterdam study, that hypertension is significantly associated with new IPH and new calcifications over a 4 year period (OR: 3.87, 95% CI: 1.90-7.90; OR: 2.20, 95% CI: 1.07-4.40, respectively), while higher levels of cholesterol were associated with LRNC progression (OR: 1.40, 95% CI: 1.10-1.70).…”
Section: Relation Between Plaque Composition and Clinical Risk Factorsmentioning
confidence: 91%
“…Diabetes is known to play an important role in stroke. The Rotterdam Study showed that IPH is associated with increased serum insulin levels but not with increased glucose levels [ 42 ]. Previous studies have also found that diabetes was highly associated with lipid-rich necrotic cores (LRNC) of plaques and that the volume ratio of LRNC > 22.0% in carotid plaques could be an independent risk factor for acute cerebral infarction [ 43 ].…”
Section: Discussionmentioning
confidence: 99%